Pengaruh Model Problem Based Learning terhadap Self-Confident dan Hasil Belajar Siswa - Erlita Khoirun Nisa; Fitria Wulandari (Proceedings of The ICECRS, 2019)
That many students have difficulties in understanding the materials is conveyed by the teachers in addition to low self-confidence. The importance of self-confidence is not supported by the facts. Therefore, this research aims to improve the students' self-confidence and student learning outcomes by using Problem Based Learning Model in SDN 1 . Design used is Quasi Experimental Design. The form is None Equivalent Control Design Group. In this design, the researchers used two groups, namely, control group and experimental group. Class A is the experimental class, while class B is the control class. The findings show that through Poblem based Learning, both students' self confidence and achievement are improved.